Action capability constrains visuo‐motor complexity during planning and performance in on‐sight climbing. (30th August 2020) - van Knobelsdorff, Marlene H.; van Bergen, Nikki G.; van der Kamp, John; Seifert, Ludovic; Orth, Dominic
Abstract : The capability to adapt to changing conditions is crucial for safe and successful performance in physical activities and sports. According to the affordance‐based control perspective, individuals act in such a way as to take into account the limits of their capability to act. However, it is not clear how strength interacts with skill in shaping performer‐environment interactions. We, therefore, determined whether fingertip strength influences patterns of gaze and climbing behavior on new routes of ever‐increasing difficulty. We expected that comparatively weaker climbers would show less complex behavior because of an inability to perceive and act. Stronger climbers would show more complex visuo‐motor behavior because more opportunities for action remain, even as route difficulty increases. For very strong climbers the route would not be challenging enough, and less complex patterns suffice. Twenty climbers, ranging from lower grade to elite level participated. Maximum fingertip strength was obtained. Participants previewed and then climbed two separate 3 m long traverses, gradually decreasing in edge depth. Gaze and hip positions were collected for subsequent computation of gaze transition entropy (during preview) and hip displacement entropy (during climbing). Data revealed statistically significant curvilinear relationships between both fingertip strength and gaze transition entropy, and fingertip strength, and hip displacement entropy. Visuo‐motor complexity is scaled by how close the individual must act relative to boundaries of what the environment affords and does not afford for action given the individual constraints. Future research should examine in greater detail relationships between action capabilities and functional movement variability.